Phenological cycle of hops cultivars, in the second production year in Parana State - Rockenbach, Bianca; Rauber, Diogo Renan; Fogaça, Luciana Alves; Dalastra, Idiana Marina; Hofstetter, Renata Edicler (Scientia Agraria Paranaensis, 2024)
The hops (Humulus lupulus L.) are a perennial herbaceous plant. Commercially, cultivars are classified as plants of American and European origin. Considering that there is no scientific data on the cultivation and productive capacity of hops in Toledo, the aim of this study was to study the phenological cycle of three cultivars in their second year of production. The research was carried out in the second year of cultivation, 2023/2024, at the Experimental Farm of the Pontifical Catholic University of Paraná, Toledo Campus. Plants of three hop cultivars (Magnum, Hallertauer Mittelfrüeh and Comet) were grown in a V system in a randomized block design, with six plants in each plot. After the stimulus to overcome dormancy in September/October, sprouting began and the phenological stages of the crop were assessed weekly from October/2023 to May/2024. The parameters assessed were: the start of sprouting, the emission of lateral branches, the start of flowering, the formation of cones and the start of the harvest, following a phenological scale. The phenological characterization showed that the Mittelfrüeh cultivar had the longest vegetative period compared to the other cultivars, while the Comet and Magnum cultivars were similar in terms of the total number of days to complete the cycle, with a difference between the number of days for their phenological phases. From the data obtained, it can be concluded that the hop cultivars Comet and Magnum both completed their cycle after 126 days, and H. Mittelfrüeh showed a longer period to complete its cycle, 139 days, under the soil and climate conditions of Toledo-Paraná, Brazil.